Exhumation of the Koktokay rare-metal pegmatite group in the China Altai: insights from low-temperature thermochronology of the No. 3 pegmatite and Aler S-type granitic batholith - Wang, Haoyu; Ren, Guangming; Tang, Yong; Zhang, Hui; Lv, Zhenghang; Huang, Zhilong (Frontiers in Earth Science, 2025)
The China Koktokay Pegmatite Group is an important metallogenic region where major rare-metal ores are mined. Here, we present new low-temperature thermochronological data to contribute to the understanding of the Koktokay Pegmatite Group’s exhumation and preservation history. Apatite U–Pb ages of ∼176 Ma, zircon fission-track ages of ∼150 Ma, zircon (U–Th)/He ages of ∼82–52 Ma, apatite fission-track ages of ∼69–49 Ma, and apatite (U–Th)/He ages of ∼90–52 Ma were obtained from three samples of the No. 3 pegmatite and the contemporaneous Aler granitic batholith in the Koktokay area. Our thermochronological data and inverse thermal history modeling reveal a moderate-to-rapid basement cooling phase during the Cretaceous (∼150–65 Ma), with an average cooling rate of ∼1.53 °C–1.06 °C/Ma. It is envisaged that this phase eventually uplifted and exhumed the pegmatite group, with erosion in the Cenozoic era being limited. Combined with previously published geochronological and thermochronological data, a multi-stage cooling history for the pegmatite group can be established. Following its magmatic–hydrothermal formation in the Late-Triassic (∼220–200 Ma), two phases of accelerated regional cooling (i.e., in the late Triassic to Early Jurassic, ∼200–180 Ma; and the mid-Jurassic to Late Jurassic, ∼176–150 Ma) can be recognized. The intense cooling in the Cretaceous is associated with the final exhumation of the pegmatite group to the surface, and some Li–Ru–Cs-mineralized pegmatites formed at the distal end of the Koktokay Pegmatite Group may have been exhumed and denuded. Furthermore, we propose a relatively intense denudation of the Koktokay Pegmatite Group, which is unfavorable for the preservation of rare-metal pegmatite bodies.